PROBIOTIC PROPERTIES OF STRAINS OF LACTOBACILLUS PLANTARUM ISOLATED FROM FERMENTED PRODUCTS - О. М. Василюк; І. Л. Гармашева; Н. К. Коваленко (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2014)
Aim. To study probiotic properties of the strains Lactobacillus рlantarum, isolated from the national fermented foods of plant and animal origin of different regions of Ukraine. Methods. The ability of strains L. plantarum to adhere was studied on the cells of human buccal epithelium. The ability to filmformation of strains L. plantarum was studied in plastic plates. We investigated the survival of L. plantarum in the conditions of the gastrointestinal tract: resistance to lysozyme, gastric juices and bile salts. Result. Probiotic properties of 24 strains L. рlantarum has been studied. These strains have a wide range of antagonistic action on opportunistic microorganisms used and proved to be sensitive to the clinically important antibiotics. Index adhesion of the lactobacilli ranged from 3.63 ± 0.38 to 30.11 ± 1.47 and didn`t depend on the source of strains isolation. Most of the studied strains (79%) had the average ability to form biofilms. Gastric juice was one of the most aggressive factors of the gastrointestinal tract, in its action, growth had 42% of the studied strains. L. plantarum resistant to lysozyme and to 0.3% bile salts have been determined. Conclusions. The probiotic properties of 24 strains of L. plantarum were investigated and analyzed. Selected two strains of L. plantarum 1047s and L. plantarum 691ch, which may be promising for use in oral probiotic preparations.